Highly efficient selection of epitope specific antibody through competitive yeast display library sorting - Puri, Vinita (Landes Bioscience, 2013)
Combinatory antibody library display technologies have been invented and successfully implemented for the selection and engineering of therapeutic antibodies. Precise targeting of important epitopes on the protein of interest is essential for such isolated antibodies to serve as effective modulators of molecular interactions. We developed a strategy to efficiently isolate antibodies against a specific epitope on a target protein from a yeast display antibody library using dengue virus envelope protein domain III as a model target. A domain III mutant protein with a key mutation inside a cross-reactive neutralizing epitope was designed, expressed, and used in the competitive panning of a yeast display naïve antibody library. All the yeast display antibodies that bound to the wild type domain III but not to the mutant were selectively sorted and characterized. Two unique clones were identified and showed cross-reactive binding to envelope protein domain IIIs from different serotypes. Epitope mapping of one of the antibodies confirmed that its epitope overlapped with the intended neutralizing epitope. This novel approach has implications for many areas of research where the isolation of epitope-specific antibodies is desired, such as selecting antibodies against conserved epitope(s) of viral envelope proteins from a library containing high titer, high affinity non-neutralizing antibodies, and targeting unique epitopes on cancer-related proteins.